Estrategias de información y educación sobre entornos alimentarios saludables, implementadas por la Comisión Intersectorial de Seguridad Alimentaria y Nutricional (CISAN) y las Instituciones Educativas de Secundaria en Neiva – Huila. (2023)
This research proposal is based on recognizing the relevance that has currently charged the right to healthy eating, due to the high rates of mortality from non-communicable diseases that occur around the world, such as result of the consumption of ultra-processed foods and sugary drinks. The aforementioned problem has led to the legislative agenda in different countries Focus your efforts on promoting healthy eating habits. A clear example of this, is law 2120 of 2021 of the Congress of the Republic of Colombia, where establish measures to prevent non-communicable diseases and promote healthy environments healthy foods, through information and education strategies that permeate different social settings, but with special emphasis on educational institutions public and private. Taking into account the above, the general objective of this research analyze the information and education strategies contained in Law 2120 of 2021, on healthy food environments, in secondary educational institutions in Neiva – Huila. To achieve the stated purpose, a methodology has been designed with mixed approach, and the use of documentary information collection techniques and survey.